2019
DOI: 10.13189/ujer.2019.071118
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Entrepreneurship Education in Higher Learning Institutions in Southeast Asia

Abstract: Many countries have invested in entrepreneurship education through programs and trainings especially in the Higher Learning Institutions (HLIs). This paper aims to systematically review the outcome of entrepreneurship education (EE) in the higher learning education by reviewing the latest ten-year published records in Southeast Asian countries. The study's primary source of data were research articles published from 2009 to 2018 in English written peer-reviewed journals on Web of Science and Scopus database. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The model illustrades the pattern of relationships between variables, so that the majority of hypotheses can prove the relationship from the education system to the formation of a circular economy perception. In general, the pattern of the relationship between entrepreneurial education and entrepreneurial intentions is in line with previous studies in Austria, Ghana, Indonesia, China, and Malaysia e.g., Denanyoh et al, (2015); Kaijun & Sholihah, (2015); Maresch et al, (2016); Othman & Othman, (2019), and (Masri et al, 2021). Regarding green entrepreneurship.…”
Section: Discussionsupporting
confidence: 90%
“…The model illustrades the pattern of relationships between variables, so that the majority of hypotheses can prove the relationship from the education system to the formation of a circular economy perception. In general, the pattern of the relationship between entrepreneurial education and entrepreneurial intentions is in line with previous studies in Austria, Ghana, Indonesia, China, and Malaysia e.g., Denanyoh et al, (2015); Kaijun & Sholihah, (2015); Maresch et al, (2016); Othman & Othman, (2019), and (Masri et al, 2021). Regarding green entrepreneurship.…”
Section: Discussionsupporting
confidence: 90%
“…Basically, an important role of entrepreneurial education is needed to support nascent or candidate entrepreneurs. It improves student engagement and intention in entrepreneurship [20], [21]. Even, one-day environmental values may appeal in line with the growing intention of sustainable entrepreneurship among young people [22].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Despite the numerous studies conducted both locally and abroad that have shown that entrepreneurship education has helped to change the attitudes of graduates towards wanting to be self-employed (Ronstadt, 1987;Katz, 2003;Othman & Othman, 2019), several studies have also highlighted the need to improve further entrepreneurship education in Malaysia (Cheng, Chan & Mahmood, 2009;Mansor & Othman, 2017). For instance, a large-scale study carried out by Yusuf and Kamil (2015), which reviewed the entrepreneurship education practices of 20 public universities in Malaysia, found that these programmes suffered a lack of funding, a weak support system, ambiguity in their policies and objectives, and an ineffective delivery mode.…”
Section: The Need To Improve Entrepreneurship Education In Malaysiamentioning
confidence: 99%